Sustainable Design and Construction Activity as Element for Green Highways in Tropical Climate - Che Ahmad, Asmalia; Illiana Husin, Nur; FarritaMohd Kamar, Izatul; Azfahani Ahmad, Nur (International Journal of Engineering and Technology, 2018)
In Malaysia, the National Green Technology Plan (NGTP) was launched in 2009 as the main agenda to promote green technology initiatives. Various green initiatives have been taken to support global efforts in maintaining the worldâ€™s ecological balance. However, most green initiatives that have been implemented in this country have been mainly related to buildings. Reviews of the literature revealed that tropical countries still lack studies on green highway project development. One of the elements of a green highway is the â€˜Sustainable Design and Construction Activityâ€™. Hence, this research has been carried out in order to determine the criteria and sub-criteria intended for the element of Sustainable Design and Construction Activity for green highways in a tropical climate. This research was under taken using the exploratory mixed method which consisted of a qualitative aspect for the preliminary survey and a quantitative aspect for the main study using a questionnaire as the research instrument. 10 experts were interviewed for the preliminary survey, whilst 143 respondents from local authorities and highway concession companies related to highway development and construction were involved for the main survey. The main data collection was analysed by using Factor Analysis. It was found that 6 criteria and 31 sub-criteria were related to the â€˜Sustainable Design and Construction Activityâ€™ element of green highways. The criteria were Pollution Prevention, Life Cycle, Noise Mitigation, Infrastructure Planning, Design Innovation, and Quality Management. These criteria and sub-criteria are significant enough to be used as an indicator in assessing green highways in a tropical climate under the element of â€˜Sustainable Design and Construction Activityâ€™. Â Â